Supervisory Control and Data Acquisition Testbed for Research and Education - Stranahan, John; Soni, Tapan; Heydari, Vahid (2019 IEEE 9th Annual Computing and Communication Workshop and Conference (CCWC), 2019)
Supervisory Control and Data Acquisition (SCADA) systems have been in use for decades. They provide remote management and monitoring capabilities for Industrial Control Systems (ICS) such as power plants, trains, water treatment plants, dams, and many other applications. In recent years, SCADA systems have been targets by cyber-attackers. The Mod-bus TCP/IP protocol which is a standard communication protocol, used by many SCADA systems for network communication, is not secure. In this paper, a design and implementation of a custom SCADA testbed to provide an active hands-on environment, is proposed. It's goal is to sparks students' enthusiasm for learning and build a strong foundation that will lead to further interest in the subject matter. This project was completed by two undergraduate students over six months and the total materials budget was less than 6,000.00. It is a good example for other schools who are interested in having a cost-effective custom ICS testbed for research and educational purposes.